2018
DOI: 10.1111/dom.13557
|View full text |Cite
|
Sign up to set email alerts
|

Effect of switching from pioglitazone to the sodium glucose co‐transporter‐2 inhibitor dapagliflozin on body weight and metabolism‐related factors in patients with type 2 diabetes mellitus: An open‐label, prospective, randomized, parallel‐group comparison trial

Abstract: The effects of dapagliflozin (DAP) and pioglitazone (PIO) on body weight and glycaemic control were compared in patients with type 2 diabetes mellitus. Seventy‐one patients on PIO were either switched to DAP (n = 36) at 5 mg per day or continued on PIO (n = 35). Primary endpoints were superiority of body weight loss and non‐inferiority of HbA1c level after 24 weeks with DAP. Body weight decrease was greater with DAP than with PIO (75.3 ± 14.9 to 71.3 ± 15.1 kg vs. 74.7 ± 13.8 to 75.2 ± 13.9 kg; P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The present study was a secondary analysis of our original multicenter, open-label, prospective, randomized, parallel-group comparison trial 9 . All patients provided written informed consent before enrollment.…”
Section: Study Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was a secondary analysis of our original multicenter, open-label, prospective, randomized, parallel-group comparison trial 9 . All patients provided written informed consent before enrollment.…”
Section: Study Overviewmentioning
confidence: 99%
“…All patients provided written informed consent before enrollment. The detailed rationale and protocol of the original trial have been described previously 9 , and are summarized below. Eligible participants included patients with type 2 diabetes mellitus, aged 20-80 years, 6.5-8.5% of glycated hemoglobin (HbA1c), ≥23 kg/m 2 of body mass index (BMI), estimated glomerular filtration rate ≥45 mL/min/1.73 m 2 and treatment with PIO for >12 weeks undergoing outpatient treatment at seven sites in Hokkaido, Japan.…”
Section: Study Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that SGLT2i improved insulin sensitivity, but the degree of improvement varied among type 2 diabetes patients 7 10 . However, other reports showed that SGLT2i did not change insulin sensitivity 17 19 . In addition, the relation between protein-enriched diet and insulin sensitivity in type 2 diabetes remains obscure.…”
Section: Discussionmentioning
confidence: 89%
“…Recent clinical trials have shown that improving metabolic status in HFrEF patients with pre-diabetes and T2DM with glucagon-like peptide-1 [GLP-1] analogue (liraglutide) [57], sodium-glucose cotransporter-2 [SGLT2] (empagliflozine) [58][59][60], was associated with a tendency to NT-proBNP serum level decrease as a secondary surrogate end point, cardiac protective effect, and beneficial CV outcomes. In contrast, among patients with prediabetes and T2DM without HF serum levels of NT-proBNP remained unaltered regardless of improving glucose homeostasis and decreased CV risk [61]. Interestingly, the change in NT-proBNP serum levels correlated negatively with baseline NT-proBNP levels in T2DM [62].…”
Section: Controversial Prognostication Abilities Of Natriuretic Peptides In Clinical Trials Among T2dm Patientsmentioning
confidence: 89%